Identification of metastasis-associated protein 1 (MTA1) as a new molecular marker for canine urothelial carcinoma - Campanelli, Gisella; Waxner, Noah; Parkhomovsky, Nema; Mak, Chun Kuen; Yin, Ji-Hang; Lin, Susanne Je-Han; Vanderstichel, Raphael; Yang, Ching; Levenson, Anait S. (Frontiers in Veterinary Science, 2025)
BackgroundAlthough metastasis-associated protein 1 (MTA1) is known to play a role in cancer invasion and metastasis of various cancers, the clinical significance of its expression in canine urothelial carcinoma (UC) has not been explored. We sought to evaluate the expression of MTA1, cyclooxygenase 2 (COX2) and E-cadherin (E-cad) in association with clinicopathological parameters in clinical samples of canine UC.MethodsWe retrospectively analyzed UC tissues from 28 canine patients using immunohistochemistry for Ki67, CD31, MTA1, COX2, and E-cad staining. Statistical significance for marker staining intensities was evaluated by ANOVA or Student’s t-test. The correlation between molecular markers in canine UC samples detected by IHC and clinicopathological features was calculated by the Wilcoxon (Mann–Whitney) and Kruskal-Wallis tests. Western blot analysis was performed for detection of EMT markers in canine cell lines.ResultsWe show that MTA1 and COX2 are overexpressed in canine UC samples compared to normal canine bladder samples, whereas E-cad levels are higher in normal bladder. The results demonstrated that MTA1 expression correlated with aggressive clinicopathological features such as high tumor-grade, muscular/vascular invasion, and metastasis. The expression of MTA1 differed in tumors depending on their localization, with the highest being in the urethra adjoining the prostate. Unexpectedly, higher E-cad levels were detected in metastatic tumor cells compared to primary tumor cells.ConclusionThese findings suggest that MTA1 may represent a key upstream effector tightly associated with COX2 and E-cad-mediated events in canine UC. Accordingly, MTA1 may be considered a feasible interceptive and therapeutic target for canine UC treatment.